"Stardom", "aging" e corporeità nel cinema italiano dei primi anni Ottanta. La ricezione di Stefania Sandrelli ne "La Chiave" di Tinto Brass (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
This contribution deals with one of the most famous films by Tinto Brass, La chiave (1983), played by Stefania Sandrelli. The film represented for Sandrelli, who was thirty-seven years old at the time of film’s release, a turning point in her artistic parable. The contribution intends to reconstruct a part of the reception of the film to highlight how some discursive operations have been spread around the aged image of the diva. In addition, the question of aging will be explored in relation to the case of a celebrity like Sandrelli, accompanied from the very beginning of her career by reflections and speeches that consider aging ahead of time. Ultimately, the case of La chiave, through Sandrelli, will give the opportunity to reflect on the forms of reception of the issue of aging, in relation to the sexualization of female performers, in a specific context of the history of the representation of sexuality in Italy.